2009
DOI: 10.1016/j.cellbi.2008.10.009
|View full text |Cite
|
Sign up to set email alerts
|

Tumor–stroma interactions influence cytokine expression and matrix metalloproteinase activities in paired primary and metastatic head and neck cancer cells

Abstract: This study evaluates the effects of gingival fibroblasts, type I collagen and autocrine/paracrine elements on cytokine expression in paired primary and metastatic human squamous cell carcinoma (HNSCC) cell lines. Additionally, the effects of IL-1alpha, IL-1beta, IL-6, TNF-alpha, TGF-beta and HGF on MMPs and cell invasion were investigated. RT-PCR results indicated the presence of mRNAs for IL-1alpha, IL-1beta, IL-6, TNF-alpha, and TGF-beta in primary and metastatic HNSCC cell lines but high expression of cytok… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0
3

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 26 publications
0
29
0
3
Order By: Relevance
“…Similarly, direct injection of human MSC into ischemic hearts decreased fibrosis, left ventricular dilation, apoptosis, and increased myocardial thickness with preservation of systolic and diastolic cardiac function without evidence of myocardial regeneration. MSCs appear to achieve this improved function by increasing acutely the cellularity and decreasing production of extracellular (25,35) .…”
Section: B4) Beneficial Remodeling Of the Extracellular Matrixmentioning
confidence: 99%
See 2 more Smart Citations
“…Similarly, direct injection of human MSC into ischemic hearts decreased fibrosis, left ventricular dilation, apoptosis, and increased myocardial thickness with preservation of systolic and diastolic cardiac function without evidence of myocardial regeneration. MSCs appear to achieve this improved function by increasing acutely the cellularity and decreasing production of extracellular (25,35) .…”
Section: B4) Beneficial Remodeling Of the Extracellular Matrixmentioning
confidence: 99%
“…Evidence also exists that both endogenous and exogenous stem cells are able to "home" or migrate into the area of injury from the site of injection or infusion (26,30,(32)(33)(34)(35)(36)(37)(38) . MSC in the bone marrow can be mobilized, target the areas of infarction, and differentiate into target tissue type.…”
Section: B3) Anti-apoptotic and Chemotactic Signalingmentioning
confidence: 99%
See 1 more Smart Citation
“…CAFs have been induced from regular fibroblasts, and even from mesenchymal stem cells, via treatment with carcinoma cell-derived medium (17) or a co-culture model (18). In addition, previous studies have demonstrated that co-culture with CAFs changes the level of secretion of numerous cytokines from carcinoma cells (19,20), thus, giving them a higher potential for invasion and metastasis. The possibility of the two cell types mutually influencing each other is one of the advantages of the Transwell co-culture model, and the background for selecting it for use in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Various studies have shown that patients with HNSCC commonly overexpress cytokines, including IL-1, IL-6, tumor necrosis factor (TNF)-α and TNF-β (25,26). Among others, IL-6 has been shown to be elevated in HNSCC cell lines of metastatic origin compared with those cultivated from the primary tumor lesion (19). Therefore, an IL-6 assay was integrated into the present study, as increased levels of IL-6 indicate a higher potential for tumor proliferation and metastasis.…”
Section: Discussionmentioning
confidence: 99%